Gamification in Online Language Learning: The Effect of Quizizz on Students’ Vocabulary Knowledge - Caroline V. Katemba; Jonathan Hamonangan Tobing (LPPM Universitas Advent Indonesia, 2026)
This study examines vocabulary improvement through Quizizz games delivered via Zoom, comparing female and male Grade 7 students. Using a quantitative comparative design, 68 students (33 females, 35 males) completed pre- and post-tests. Female scores improved from 74.94 to 95.03, while male scores increased from 73.03 to 90.20. Both groups showed significant vocabulary gains, with statistical analysis indicating a meaningful difference between genders (p < 0.05). Overall, Quizizz proved effective in enhancing vocabulary acquisition and demonstrated the value of interactive, game-based learning in online environments.